Pengaruh Ketidaksetaraan Gender terhadap Pertumbuhan Ekonomi Negara Berkembang di Asia - Sinta Aulia Putri; Joan Marta (Universitas Negeri Padang, 2025)
This study aims to examine the effect of gender inequality in education participation, labor force participation rate, and health on economic growth. This study uses macro data from the World Bank. This study analyzes 12 developing countries in Asia from 2005 to 2020. The method used is panel data regression with Fixed Effect Model. The results showed that gender inequality in secondary education participation and higher education participation had a significant negative effect on economic growth. Health has a significant positive effect, while labor force participation has an insignificant negative effect. These findings highlight the importance of creating gender equality to improve economic growth.